Experimental investigations on the correlations between the structure and thermal‐electrochemical properties of over‐discharged ternary/Si‐C power batteries. (19th September 2021) - Zhang, Jiangyun; Li, Xinxi; Zhang, Guoqing; Wu, Hongwei; Shao, Dan; Ge, Xin; Huang, Qiqiu; Zhen, Zhicheng; Chen, Xuanzhuang
Summary: The thermal safety of power lithium‐ion batteries (LIBs) has seriously affected the booming development of electric vehicles (EVs). Especially, owing to the requirement of high energy density, thermal runaway (TR) easily occurs in LIBs, resulting in a higher heat generation rate. Over‐discharging is recognized as a common cause for TR. In the present research, the correlations between the structure and thermal‐electrochemical properties of an over‐discharged ternary/Si‐C battery at room and high temperatures were investigated. The heat generation mechanisms of the batteries due to the maximum surface temperature and peak temperature difference variations during fast charging and discharging processes were investigated. Moreover, the electrochemical performances parameters of the batteries, such as voltage changing trend, discharge time, discharge capacity, internal resistance, electrochemical impedance spectroscopy (EIS) spectra, were analyzed. When the battery was discharged at 2.0C and 55°C, its maximum temperature and highest temperature difference reached 91.34°C and 13.24°C, respectively, finally resulting in a sharp decline in electrochemical performance. Furthermore, the root reasons for performance degradation and heat generation intensification of the over‐discharged battery were analyzed by scanning electron microscopy and X‐ray diffraction. The cause of the aforementioned phenomenon is due to irreversible damage to the electrode materials. This research not only reveals the relevant relationship between the thermal behavior and the microscopic structure of the over‐discharged ternary/Si‐C battery under various temperature conditions but also provides valuable insights for improving the safety of LIBs modules even packs. Abstract : An overdischarged battery and a normal battery, both using ternary/Si‐C electrodes, were investigated and analyzed synergistically through thermal behaviors and electrochemical characteristics under various conditions, and the root cause is attributed to the crystal structure destruction and electrode materials aggregation.